ANALISIS PERMASALAHAN PENDIDIKAN ANAK USIA DINI DALAM MASYARAKAT INDONESIA - Lilis Suryani (Jurnal Ilmiah Visi, 2007)
Children are the future of a nation. This statement is not an exaggeration, it is the truth. Children would grow up and be potential leaders for their nation. The development of a country, then depends on them someday. So, it is important for us that we should pay more attention to their early childhood education right now. Paying more attention to this phase of education means improving the quality of human resources of a nation for the future. Unfortunately, few people are interested in becoming educators for early childhood education. Besides, most parents in Indonesia still do not realize how important early childhood education is for every individual child as well as for the future of our nation.